Enhancing Mothers' Involvement in Child Health Service: A Macro-Level Intervention in RT 03/RW 05, Pabelan - Azahra, Fathia Fitri; Arsita, Dina; Kumara, Kusuma Arum Dyana; Karyani, Usmi (Universitas Muhammadiyah Surakarta, 2025)
This study addresses the low participation of mothers in accompanying their children to Posyandu (integrated health service posts) in RT 03/RW 05, Pabelan Village. Observations and interviews revealed that many mothers are unable or unwilling to attend due to work, household fatigue, or assumptions that childcare duties can be delegated to others. These behaviors impact the quality of child health services, including missed emotional support, reduced direct parental involvement, and decreased access to vital health information. Using Bronfenbrenner's ecological systems theory as a framework, the researchers conducted a macro-level intervention in the form of structured health counseling sessions targeting mothers of young children. Data collection methods included semi-structured interviews, non-participant observation, and community advocacy. The intervention focused on increasing awareness of the importance of maternal presence at Posyandu through community-based education, leaflets, and collaboration with local leaders and cadres. The results showed increased maternal knowledge, improved attitudes toward Posyandu, and strengthened peer support among mothers. The study concludes that community-oriented health education can effectively enhance maternal involvement, which is essential for ensuring optimal child development and access to early health services.